Trajectories and correlates of poor mental health in India over the course of the COVID-19 pandemic: a nationwide survey - Jinkook Lee; Joyita Banerjee; Marco Angrisani; David E Bloom; Simone Schaner; Sarah Petrosyan; Sharmistha Dey; Emma Nichols; Pranali Khobragade; Aparajit B Dey (BMJ Global Health, 2024)
Introduction The COVID-19 pandemic had large impacts on mental health; however, most existing evidence is focused on the initial lockdown period and high-income contexts. By assessing trajectories of mental health symptoms in India over 2 years, we aim to understand the effect of later time periods and pandemic characteristics on mental health in a lower-middle income context.Methods We used data from the Real-Time Insights of COVID-19 in India cohort study (N=3709). We used covariate-adjusted linear regression models with generalised estimating equations to assess associations between mental health (Patient Health Questionnaire (PHQ-4) score; range 0–12) and pandemic periods as well as pandemic characteristics (COVID-19 cases and deaths, government stringency, self-reported financial impact, COVID-19 infection in the household) and explored effect modification by age, gender and rural/urban residence.Results Mental health symptoms dropped immediately following the lockdown period but rose again during the delta and omicron waves. Associations between mental health and later pandemic stages were stronger for adults 45 years of age and older (p<0.001). PHQ-4 scores were significantly associated with all pandemic characteristics considered, including estimated COVID-19 deaths (PHQ-4 difference of 0.10 units; 95% CI 0.06 to 0.13), government stringency index (0.14 units; 95% CI 0.11 to 0.18), self-reported major financial impacts (1.20 units; 95% CI 1.09 to 1.32) and COVID-19 infection in the household (0.36 units; 95% CI 0.23 to 0.50).Conclusion While the lockdown period and associated financial stress had the largest mental health impacts on Indian adults, the effects of the pandemic on mental health persisted over time, especially among middle-aged and older adults. Results highlight the importance of investments in mental health supports and services to address the consequences of cyclical waves of infections and disease burden due to COVID-19 or other emerging pandemics.